FAMILY SOCIAL SUPPORT IN SOLVING ABILITY PROBLEMS IN BIPOLAR DISORDER PATIENTS - Hadifah Nurul Fikriyah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
Bipolar disorder is a disorder of sudden mood swings. Changes that occur between times of depression or sadness can turn to joy, within a relatively short time. These changes are based on the moods felt by bipolar sufferers and these changes are comprehensive in everyday life, the consequences felt by bipolar patients make them need to receive support, especially the support of their closest environment, namely family. This study intends to find out how the role of the family in helping bipolar patients solve their problems. This study uses a qualitative method with a literature study approach. The data analysis process is carried out by reviewing related journals and drawing conclusions. Through this research, it is hoped that it can illustrate that good family social support, especially emotionally, is needed by bipolar patients in solving their problem.